The awkward adolescence of archaeological science. (April 2015) - Killick, David
Abstract: The rapid growth of archaeological science (and of the Journal of Archaeological Science ) over the last 15 years has changed archaeology worldwide. New methods of analysis have allowed archaeologists to pose many new questions, and have made it possible to revisit many old ones. In spite of its many successes, archaeological science is not yet a mature field of science, for it has yet to attract adequate funding, has not solved the problem of how to reproduce itself (issues of training and employment), and still struggles with quality control. These are however all problems of archaeological science in rich nations. Looking beyond these, a particularly troubling issue is the growing inequality of access to archaeological science. Archaeologists in poorer nations are often aware of the growing importance of scientific techniques in archaeological research, but cannot obtain access to them. Archaeological scientists also need to be aware of potential political sensitivity of their work, and to work to build trust. Highlights: Archaeological science has grown faster than any other subfield of archaeology since 2000. New scientific methods have generated many new questions, and revived old ones. Flawed studies are still published because of the scarcity of qualified reviewers. There is a problem with quality control in some areas of archaeological science. Archaeological scientists in rich nations should do more to help archaeologists in poor nations.